Pathfinding a new path of islam: reconstruction of Indonesian Islamic thoughts within the new order epoch - Fachry Ali (Puslitbang Lektur Khazanah dan Keagamaan Badan Litbang dan Diklat Kemenag RI, 2011)
wt/1/nr,c.1